(untitled) (Eurasian Medical Research Periodical, 2023)
Triple negative breast cancer (TNBC) is characterized by the absence of estrogen receptors (ER), progesterone receptors (PR) and HER-2/neu expression. TNBC is a heterogeneous disease with an aggressive course, with a high risk of early local and distant metastasis to the visceral organs and/or brain. Relapse usually occurs between the 1st and 3rd years, and most patients die within 5 years of the initial diagnosis. Studies have shown that young women predominate among patients with TNBC. Triple negative breast cancer is often associated with BRCA mutations, especially when diagnosed at a young age. Chemotherapy remains the main treatment for patients with TNBC due to the lack of specific drug targets (hormone receptors or HER-2 amplification). However, at present there are no uniform standards for the treatment of patients with TNBC metastases. An important task remains the further study of new regimens and drug regimens for patients with generalized triple-negative breast cancer, which can improve the immediate and long-term results of their treatment